2018
DOI: 10.3390/ijms19123801
|View full text |Cite
|
Sign up to set email alerts
|

YAP Activation Drives Liver Regeneration after Cholestatic Damage Induced by Rbpj Deletion

Abstract: Liver cholestasis is a chronic liver disease and a major health problem worldwide. Cholestasis is characterised by a decrease in bile flow due to impaired secretion by hepatocytes or by obstruction of bile flow through intra- or extrahepatic bile ducts. Thereby cholestasis can induce ductal proliferation, hepatocyte injury and liver fibrosis. Notch signalling promotes the formation and maturation of bile duct structures. Here we investigated the liver regeneration process in the context of cholestasis induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 53 publications
1
27
1
Order By: Relevance
“…Multiple researches recognized YAP1 as an profibrogenic factor, however due to different liver disease models, the role of YAP1 in hepatic anti-fibrosis may be controversial. YAP1 activation was previously recognized as an important role to promote liver regeneration and alleviate liver injury in cholestasis by two studies (Bai et al, 2012;Tharehalli et al, 2018). Besides a resent study has shown that activation of YAP could attenuate hepatic damage and fibrosis in liver ischemiareperfusion injury (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Multiple researches recognized YAP1 as an profibrogenic factor, however due to different liver disease models, the role of YAP1 in hepatic anti-fibrosis may be controversial. YAP1 activation was previously recognized as an important role to promote liver regeneration and alleviate liver injury in cholestasis by two studies (Bai et al, 2012;Tharehalli et al, 2018). Besides a resent study has shown that activation of YAP could attenuate hepatic damage and fibrosis in liver ischemiareperfusion injury (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Hence, in the quest for new drugs to impede liver fibrosis and cirrhosis, it may be useful to search for other non-Hippo related signaling pathways that regulate YAP activation in hepatic stellae cells. Signaling pathways that have so far been implicated include the TGF-β1 signaling pathway (Lee et al, 2016;Yu et al, 2019), the Wnt/β-catenin signaling pathways (Yu et al, 2019), the Notch signaling pathway (Tharehalli et al, 2018) and the Hedgehog signaling pathway (Swiderska-Syn et al, 2016;Du et al, 2018).…”
Section: Role Of Yap/taz In Hepatic Differentiation and Liver Regenermentioning
confidence: 99%
“…Hence, in the quest for new drugs to impede liver fibrosis and cirrhosis, it may be useful to search for other non-Hippo related signaling pathways that regulate YAP activation in hepatic stellae cells. Signaling pathways that have so far been implicated include the TGF-β1 signaling pathway ( Lee et al, 2016 ; Yu et al, 2019 ), the Wnt/β-catenin signaling pathways ( Yu et al, 2019 ), the Notch signaling pathway ( Tharehalli et al, 2018 ) and the Hedgehog signaling pathway ( Swiderska-Syn et al, 2016 ; Du et al, 2018 ). In addition, Zhang K. et al (2016) demonstrated that uptake of omega-3 polyunsaturated fatty acids by mice ameliorates liver fibrosis by inhibiting hepatic stellae cell activation and proliferation through promotion of YAP/TAZ degradation.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 99%
“…In addition to Notch, Wnt, and Hedgehog, yes-associated protein (YAP) is a morphogen instrumental for liver regeneration following cholestatic damage. In a mouse model of ductopenia induced by liver-specific deletion of the central downstream effector of Notch signaling, the recombination signal binding protein for immunoglobulin kappa j region (RBPJ), Tharehalli and coworkers found that YAP was activated in response to the increased expression of the scaffolding protein IQGAP1 induced by bile acid accumulation and stimulated a compensatory hepatocyte transdifferentiation towards the biliary lineage (intermediate hepatobiliary cells) with upregulation of the cholangiocyte marker SOX9 [6].…”
Section: Cell Interactions In Liver Repair and Regenerationmentioning
confidence: 99%